2017
DOI: 10.1097/wco.0000000000000410
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of atrial fibrillation newly diagnosed after ischemic stroke and transient ischemic attack: advances and uncertainties

Abstract: Purpose of reviewAtrial fibrillation is being increasingly diagnosed after ischemic stroke and transient ischemic attack (TIA). Patient characteristics, frequency and duration of paroxysms, and the risk of recurrent ischemic stroke associated with atrial fibrillation detected after stroke and TIA (AFDAS) may differ from atrial fibrillation already known before stroke occurrence. We aim to summarize major recent advances in the field, in the context of prior evidence, and to identify areas of uncertainty to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 106 publications
2
55
0
6
Order By: Relevance
“…In line with previous studies [6,15], the results of the present study support the hypothesis that a variety of molecular biomarkers can potentially be used as indicators of underlying AF in CS patients. In earlier studies, the relationship between AF and biomarker levels were mostly investigated by testing individual biomarkers [8,22] or a specific biomarker selection based on their functional similarities [15]. To our knowledge, this is the first study using a multiple-biomarker approach in patients with stroke of different etiologies.…”
Section: Resultsmentioning
confidence: 99%
“…In line with previous studies [6,15], the results of the present study support the hypothesis that a variety of molecular biomarkers can potentially be used as indicators of underlying AF in CS patients. In earlier studies, the relationship between AF and biomarker levels were mostly investigated by testing individual biomarkers [8,22] or a specific biomarker selection based on their functional similarities [15]. To our knowledge, this is the first study using a multiple-biomarker approach in patients with stroke of different etiologies.…”
Section: Resultsmentioning
confidence: 99%
“…This ‘neurogenic’ AF could be a transient phenomenon and not require long-term anticoagulation, unlike ‘cardiogenic’ AF due to structural heart disease 53. Although there is insufficient supporting evidence to change clinical practice, a recent report suggested that recurrent ischaemic stroke risk in patients diagnosed with AF after stroke is low compared with that of patients known to have AF before the stroke, and similar to that in patients in sinus rhythm 54.…”
Section: Diagnosis Of Af After Strokementioning
confidence: 99%
“…Currently, the KAF is considered as the cardiogenic AF, which was mainly caused by cardiac remodeling, while AF detected after stroke (AFDAS) may composed of multiple types of AF, including the preexisting but newly diagnosed atrial brillation (cardiogenic AF) and newly emerged atrial brillation (neurogenic AF) (24). The neurogenic AF is the main type of AFDAS, which may be caused by in ammatory response and dysfunction of the autonomic regulation of cardiac rhythm (24,25). Based on this difference between mechanisms of KAF and AFDAS, the effect of AFDAS on stroke severity may also vary from that of KAF.…”
Section: Discussionmentioning
confidence: 99%